2020
DOI: 10.1101/2020.09.22.20199471
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Delayed viral clearance and exacerbated airway hyperinflammation in hypertensive COVID-19 patients

Abstract: In COVID-19, hypertension and cardiovascular diseases have emerged as major risk factors for critical disease progression. Concurrently, the impact of the main anti-hypertensive therapies, angiotensin-converting enzyme inhibitors (ACEi) and angiotensin receptor blockers (ARB), on COVID-19 severity is controversially discussed. By combining clinical data, single-cell sequencing data of airway samples and in vitro experiments, we assessed the cellular and pathophysiological changes in COVID-19 driven … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 54 publications
1
23
0
1
Order By: Relevance
“…In airway cells, the SARS-CoV-2 infection itself associates with increased ACE2 mRNA expression. 56 58 Hence, in epithelial cells obtained from nasopharyngeal and bronchial samples in patients with COVID-19, an average 3-fold increase in ACE2 expression was found in epithelial cells. 57 This correlated with INF (interferon) signals by immune cells 57 in agreement with a study that revealed the induction of ACE2 mRNA expression by interferon in human nasal epithelial and lung tissue (Figure 1 D).…”
Section: Ace2 the Connecting Link Between Bp Regulation And Sars-cov-mentioning
confidence: 97%
See 1 more Smart Citation
“…In airway cells, the SARS-CoV-2 infection itself associates with increased ACE2 mRNA expression. 56 58 Hence, in epithelial cells obtained from nasopharyngeal and bronchial samples in patients with COVID-19, an average 3-fold increase in ACE2 expression was found in epithelial cells. 57 This correlated with INF (interferon) signals by immune cells 57 in agreement with a study that revealed the induction of ACE2 mRNA expression by interferon in human nasal epithelial and lung tissue (Figure 1 D).…”
Section: Ace2 the Connecting Link Between Bp Regulation And Sars-cov-mentioning
confidence: 97%
“… 21 Treatment with RAS-blockers may protect against organ injury, for example, in the lung, by inhibiting the damaging Ang II/AT1R axis and by activation of the protective axis, particularly via the ACE2/Ang 1-7/MasR axis. Available data indicate that ACE2 mRNA 58 and importantly also ACE2 protein expression 53 are not increased in airway cells of patients treated with ACEIs or angiotensin receptor blockers (ARBs) suggesting that these drugs do not impact on the infectivity of SARS-CoV-2.…”
Section: The Role Of the Ras In The Link Between Hypertension And Covmentioning
confidence: 99%
“…Moreover, it has been suggested that underlying cardiovascular disease may promote a more severe course of COVID-19 infection [ 141 , 142 , 155 , 156 , 157 , 158 ]. In this context, a meta-analysis of 1527 COVID-19 patients showed that 17.1% of these patients were hypertensive and 16.4% had pre-existing heart disease [ 159 ].…”
Section: Updates On Sars-cov-2 Infection and Covid-19 Associationmentioning
confidence: 99%
“…Elevated CCR1 expression may enhance lung infiltration by monocytes and macrophages upon viral infection 16 , provoking a rapid and deleterious hyperinflammation as observed in COVID-19 patients suffering from severe disease 2 , 21 ( Fig.2e ). In support of this notion, single cell RNA-sequencing revealed increased levels of CCR1 and its ligands CCL2 / CCL3 in pulmonary macrophages from critical COVID-19 patients 22 , 23 . Additionally, CCL2 plasma levels showed the highest predictive value for mortality in a COVID-19 patient cohort 21 .…”
mentioning
confidence: 73%